G477(P) Non-blanching rash: thinking outside the box. (12th March 2018) - Desai, P; Yale, C; Herath, D; Tobin, J
Abstract : An 11-year-old girl presented to the Paediatric department with a non-blanching rash, which was vasculitic in appearance and tender to touch, but not pruritic. The typical feature was hyperaesthesia, starting on her left forearm. The child was well and afebrile, with no history of: musculoskeletal problems; red eyes; mouth ulcers; trauma or insect bites. The girl lived with her parents and two siblings, and had neither a past medical history nor family history of vasculitis. At initial presentation, the paediatrician corroborated the GP's working diagnosis of shingles with neuropathic pain; the patient was given an extended course of acyclovir, plus amitriptyline. During follow up, the patient reported improved pain, whilst the rash had completely subsided. However, two weeks later, the girl returned with a similar painful rash. Upon dermatological review, she received IV antibiotics for suspected chronic meningococcemia. Over the next eight months, the rash waxed and waned, and often healed completely. She received, at various stages, diagnoses of: shingles with neuropathic pain; chronic meningococcemia; segmented pigmented dermatosis; cutaneous vasculitis; atypical Henoch-Schönlein purpura; and potential urticarial vasculitis. Altogether, this patient had 13 paediatric outpatient appointments, one admission, two reviews in the acute paediatric unit and two tertiary dermatology referrals. She had 29 blood tests, and numerous urine dipsticks. Her full blood count, coagulation screen, inflammatory markers and autoimmune screen were normal. She received three courses of acyclovir, one course of antibiotics, regular analgesia, amitriptyline and six weeks of prednisolone. She also had two skin biopsies, which reported an element of purpura without any vasculitis. Given purpura without vasculitis, the revelation that our patient was a teenager going through a stressful period at school caused us to consider and discuss an exogenous cause (deliberate self-infliction). The rash's subsequent complete resolution within a few months strengthens this hypothesis. Clinicians frequently care for children with complex or unconventional presentations. In an era of defensive medicine, we request a plethora of investigations and specialist opinions before diagnoses like self-inflicted injuries are considered. This case raises ethical questions about how far we should go in our pursuit of an intellectually satisfying definitive diagnosis.